Self-reported health conditions among refugees and asylum-seekers (AS) in Italian hosting centres. (13th November 2019) - Bertoncello, C; Fonzo, M; Zanovello, S; Ferretti, S; Brunetta, R; Gallo, G; Baldo, V
Abstract: : In recent years, Italy has been facing an increase in migration flows. Migrants are vulnerable: understanding underlying conditions is essential to provide suitable assistance. We investigated health conditions of AS arrived in 2014-2016 and living in hosting centres in northeast Italy. AS filled in a multi-language questionnaire. Demographic characteristics, self-reported health status and travel conditions were recorded. Logistic regression (adjusting for age, sea/land arrival, marital status, education level), χ2 and Fisher's test were used (significance at .05). 216 AS were included, of which 98% males and 91% aged 15-34; 72% arrived by sea, of which 96% from West Africa (WA), while 94% of land arrivals were from the Indian Subcontinent (IS). 62% experienced health problems after arrival. This condition was significantly associated with sea arrival (aOR 2.9), married status (aOR 3.1) and higher education levels. Most problems involved GI tract (13%), teeth (17%) and skin (25%), being AS from WA (31%) more affected than IS (10%). STDs and alcohol were considered as health threats by more than 30% of AS, while smoking, diet and drugs were ignored; 27% and 23% declared to smoke and consume alcohol, respectively, with no substantial change compared with pre-arrival habits. 88% considered their current health good/satisfactory. While anxiety seemed to affect 10% of AS, 30% reported symptoms of depression, especially those arrived by sea (aOR 3.1) and with higher education. However, physical (94%) and mental (88%) health was considered improved/stable after arrival. Perceived health is overall good. However, AS by sea, with higher education or experiencing family breakdown suffer more from both physical and mental issues, especially depression. Long waiting times to grant refugee status and partial fulfilment of life expectations may worsen health conditions. Customised solutions in hosting centres may be encouraged, considering travel conditions and cultural background. Key messages: Migrants' health in hosting centres is good; AS by sea, married and with higher education are more at risk, especially as regards mental health; depression warning signs must not go unnoticed. AS in hosting centres represent a heterogeneous population: they may benefit from a more tailored assistance, considering differences in travel conditions, cultural background and life expectations.